First aid for generalized seizures: modern approaches and opportunities for improvement - А. А. Birkun; L. I. Dezhurny (Эпилепсия и пароксизмальные состояния, 2023)
Background. Generalized seizures are often complicated by life-threatening health problems (such as airway obstruction, suppressed respiration and severe injuries) or observed as a manifestation of sudden cardiac arrest that determines a need for rapid recognition and management of the problem. Since immediate arrival of emergency medical service (EMS) specialists to a victim is impossible in most cases, first aid (FA) provision by immediate witnesses of seizures is of paramount importance for preventing death.Objective: to analyze modern principles and approaches to FA provision for generalized seizures, to study existing organizational framework and to identify areas for improving the organization of FA provision for seizures, as well as to develop a draft domestic algorithm for distant consultation of untrained witnesses by emergency dispatchers on FA provision in generalized seizures.Material and methods. The analysis was carried out for international and national guidelines on FA, domestic and foreign scientific publications corresponding to the study topic, as well as normative legal acts regulating FA provision in Russia, foreign sets of protocols for EMS dispatchers containing instructions on FA in seizures intended for remote (by telephone) provision to witnesses of the incidents.Results. Based on the analysis of international and national guidelines on FA and existing dispatch protocols, taking into account the methodological recommendations approved by the Ministry of Health of Russia that determine general principles for receiving requests from the public by EMS dispatchers, the draft universal Russian-language algorithm for dispatcher interrogation and instruction of incident witnesses on FA provision for generalized seizures was developed. A need to modernize the domestic regulatory framework in terms of including seizures in the list of conditions for which FA should be provided, and officially approve the sequence and rules on FA provision for seizures was substantiated.Conclusion. In Russia, the organization of FA provision for generalized seizures is not optimal and requires improvement. The effect of prompt involvement of untrained witnesses of seizures in the process of providing aid is expected to be ensured by introducing a practice of consulting incident witnesses on FA provision by emergency dispatchers over the telephone. The developed universal dispatch algorithm, after its discussion and testing, could act as one of the basic components of the domestic program for FA distance support.